Is the Bible true word of God? - Deedat, Ahmed; Sjoberg, Pastor Stanley (Dubai : Islamic Propagation Center International [production company] ; Kuala Lumpur : SABA Islamic Media [distributor])
The 1st debate in Stockholm,Sweden by Sheikh Ahmed Deedat with Pastor Stanley Sjoberg
Title from container
Debate 1 in Stockholm
Speaker: Ahmeed Deedat, Pastor Stanley Sjoberg
VCD format
Keywords: Qur'an -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Islam -- Relations -- Christianity